Attitude towards the usage of electronic information resources in Medical Library, University of Jaffna, Sri Lanka. - Sivathaasan, N.; Murugathas, K.; Chandrasekar, K. (Information and Knowledge Management, 2014)
Purpose- The purpose of the study is to find out whether there are any significant mean differences among personal characteristics such as readers’ type, gender, user category, age group and the year of study towards attitude of using electronic information resources in Medical Library, University of Jaffna, Sri Lanka during the year 2013. Research Design-The study used the questionnaire as a research instrument and a total of 258 usable responses were obtained using random sampling technique. Further, the study employs independent samples t-test and One-way ANOVA (f-test) for the purpose of data analysis. Findings- The results revealed that readers' type such as academic staff and students, the year of study of the Students and user category (Lecturer, Senior Lecturer, Professor and students) have shown significant mean difference towards the attitude of usage of electronic information resources (P < 0.05). But, gender both male and female readers and age group have roughly same level of opinion, which is insignificant. Research Limitation-As the study was limited to the academic staff and medical students at the Faculty of Medicine, a challenge may occur in terms of generalization of the results widely. Originality-The findings of this research could be generalized to the studies similar to this category.
Keywords: Attitude; Electronic Information Resources; Medical Library; University of Jaffna